The Effectiveness of Eugenia Oleina in Protecting Tropical Residual Slope from Excessive Shear Failure - Youventharan, Duraisamy; Rokiah, Othman; Mohd Ari, Sulaiman; Ramadhansyah Putra, Jaya; Siti Noor Linda, Taib; Irfan Hakimie, Mohd Rodzif; Kuraisha, Kambali (Bentham Open, 2024)
Introduction: Slope stability and soil erosion are major concerns in geotechnical engineering and land management. This research investigates the relationship between soil type and root systems in stabilizing slopes. Methods: The main aim is to measure the effectiveness of Eugenia Oleina as a bioengineering technique for slope protection. Laboratory tests were conducted to measure soil shear strength, root properties, and the factor of safety (FOS) of tropical slopes before and after plant root implementation. Results: Results revealed significant differences in cohesion and angle of friction values between unrooted and rooted soil. Apart from that, it was observed that as the root diameter increased, the tensile strength decreased when the applied force increased. The FOS of unrooted soil was higher than rooted soil, indicating greater stability without any vegetation. Furthermore, this study also evaluated the use of bio-anchorage to prevent soil erosion, considering factors such as soil composition, vegetation, and external loads. Finite element analysis was carried out using Plaxis 3D simulations to assess the effectiveness of Eugenia Oleina in controlling slope erosion. Conclusion: This study contributes valuable insights in choosing suitable plant species for erosion control in tropical soil and guides soil bioengineering practices for slope stability in various soil conditions.